2012
DOI: 10.1093/jleo/ews027
|View full text |Cite
|
Sign up to set email alerts
|

Agency and Compensation: Evidence from the Hotel Industry

Abstract: We examine the relationship between employee supervision and compensation by taking advantage of the structure of the hotel industry, in which many chains have both company managed and franchised properties. Given that supervision is less rigorous at company managed establishments, we estimate differences in wages and human resource practices not only across company managed and franchised hotels within chains, but also within individual hotels as they change organizational form. While we cannot rule out the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Krueger () provides further credibility to this argument, finding that the differential impact of contractual arrangements gives managers of company‐owned units less incentive to monitor and supervise their employees. His findings were recently supported by Freedman and Kosová () who found that differences in wages and human resource practices support the agency theoretic argument that franchisees monitor their employees more closely than managers of company‐owned units.…”
Section: Literature Reviewmentioning
confidence: 77%
See 1 more Smart Citation
“…Krueger () provides further credibility to this argument, finding that the differential impact of contractual arrangements gives managers of company‐owned units less incentive to monitor and supervise their employees. His findings were recently supported by Freedman and Kosová () who found that differences in wages and human resource practices support the agency theoretic argument that franchisees monitor their employees more closely than managers of company‐owned units.…”
Section: Literature Reviewmentioning
confidence: 77%
“…Capital investment by the local franchisee should lead to less shirking as compared with company employees. Prior work supports this vertical agency argument (Beheler, Norton, and Sen ; Krueger ; Freedman and Kosová ). As such, franchisees should do a better job than managers of company‐owned units in terms of monitoring their employees.…”
Section: Literature Reviewmentioning
confidence: 87%
“…In this case, the franchisor itself does not manage the hotel, but rather leaves most day-to-day management decisions (e.g. staffing, pricing or employee pay) to the franchisee (e.g., Freedman and Kosová, 2014). Under this type of contract, the franchisee is the residual claimant of the profits from the hotel's operations (net of royalty payments and other fees paid to the franchisor).…”
Section: Contracts and Organizational Formsmentioning
confidence: 99%
“…Additionally, anecdotal evidence (Cooper, 2012) as well as our discussions with industry practitioners reveal that on-site inspections while pretending to be customers are common. Also, as Freedman and Kosová (2014) point out, in the hotel industry -unlike in other contexts (e.g., retail or restaurants) -remote technology (e.g., video-cameras) cannot be used for monitoring in order to protect the privacy of the guests. Therefore, as per standard agency theory (e.g., Rubin, 1978;Norton, 1988) the costs of monitoring local operations will be higher the more distant the operation is from the monitor.…”
Section: Initial Requirements In Franchise Hotel Agreementsmentioning
confidence: 99%
“…With nearly 5 million guestrooms, a $21.6 billion pre-tax income, and more than $128 billion dollars in revenue, the hotel industry is a prominent contributor to the U.S. economy (American Hotel & Lodging Association, 2012). This industry is driven by increasing competition, high profits, low cost-productivity, and seasonal demand (Freedman & Kosová, 2011). These characteristics are reflected by employers’ attitudes toward employees and their hiring practices regardless of hotel size, type, location, services offered, or chain affiliation.…”
Section: Agency-hired Hotel Housekeepersmentioning
confidence: 99%